Mittag-Leffler Operator Connected with Certain Subclasses of Bazilevic Functions - Ahuja, Om; ÇETİNKAYA, ASENA; Jain, Naveen Kumar (Hindawi Ltd., 2022)
In this paper, we introduce a new generalized class of analytic functions involving the Mittag-Leffler operator and Bazilevic functions. We examine inclusion properties, radius problems, and an application of the generalized Bernardi-Libera-Livingston integral operator for this function class.
Keywords: Mathematics